Complementación metodológica para el análisis de datos cuantitativos y cualitativos en evaluación educativa - Moscoloni, Nora (R.E.M.A. Revista electrónica de metodología aplicada, 2012)
En los procedimientos de triangulación metodológica, la compatibilidad de diferentes técnicas puede utilizarse para mutua verificación, sin embargo resulta difícil aprovechar las ventajas complementarias y a la vez no superponer sus debilidades. Este trabajo, referido a la evaluación de un curso de perfeccionamiento docente de características particulares, propone superar ese problema a través del análisis integrado de materiales diversos combinando análisis exploratorios multidimensionales inscriptos en la corriente francesa del análisis de datos de corte cuantitativo, con análisis de casos de tipo cualitativo. Los resultados presentados muestran cómo el primer análisis permite monitorear la selección de casos para el segundo. Compatibility between techniques is a challenge for good interpretation of results when triangulation of methods is used. It could be useful for mutual verification, nevertheless it is difficult to exploit advantages and at the same time not to superpose weaknesses. A way of avoid this problem is proposed by means of an integrated analysis combining qualitative and quantitative materials applying Multidimensional Data Analysis and Cases Analysis. Data refers to diagnostic, followed out and assessment information from a course addressed to high school teachers in Social Sciences. It was focused on the constructionist model application: learning the methodology of research and the application in the classroom; disciplinary adjustment to the Social Sciences and for last, integration of the new standpoint in a didactic proposal, were the main objectives. Distance and presence activities were proposed during a whole year, so a variety of instruments were to be designed. Results show how the Multidimensional Data Analysis allows guiding the selection of the sample for the application of Cases Analysis.